Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/bioinformatics/btaa281
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of co-evolution analysis through phylogenetic profiling reveals pathway-specific signals

Abstract: Summary The exponential growth in available genomic data is expected to reach full sequencing of a million genomes in the coming decade. Improving and developing methods to analyze these genomes and to reveal their utility is of major interest in a wide variety of fields, such as comparative and functional genomics, evolution and bioinformatics. Phylogenetic profiling is an established method for predicting functional interactions between proteins based on similarities in their evolutionary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…genes that are either conserved or lost as a group) are functionally related, often belonging to the same pathway (27–29, 31) . We have shown that both across-clade and within-clade measures of co-evolution can be informative (27, 32, 39) , and thus we computed NPPs both across all eukaryotes (Fig. 1A and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…genes that are either conserved or lost as a group) are functionally related, often belonging to the same pathway (27–29, 31) . We have shown that both across-clade and within-clade measures of co-evolution can be informative (27, 32, 39) , and thus we computed NPPs both across all eukaryotes (Fig. 1A and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work, we developed an improved version of PP that normalizes signals across hundreds of eukaryotic genomes to identify important new members of cellular and disease pathways (27–31) . As protein function and evolution are very complex (32) , co-evolution within a local lineage (i.e. mammals, vertebrates, fungi, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…For each human gene and each species, we only considered the matched gene with the highest bit score. While other good approaches are available like reciprocal blast, our method has been widely used and worked well using human and other reference genomes (Bloch et al ., 2020; Omar et al ., 2018; Tsaban et al ., 2021). To reduce the influence of random matches, the bit scores were set to 0 for matches with E-value > 1e-5.…”
Section: Methodsmentioning
confidence: 99%
“…In our recent work, we developed an improved version of PP that normalizes signals across hundreds of eukaryotic genomes to identify important new members of cellular and disease pathways ( Arkadir et al, 2019 ; Sherill-Rofe et al, 2019 ; Tabach et al, 2013a ; Tabach et al, 2013b ; Schwartz et al, 2013 ). As protein function and evolution are very complex ( Bloch et al, 2020 ), co-evolution within a local lineage (i.e. mammals, vertebrates, fungi, etc.)…”
Section: Introductionmentioning
confidence: 99%